Auditory prostheses : new horizons - Popper, Arthur N.; Fay, Richard R.; Zeng, Fan-Gang (Springer handbook of auditory research, 2012)
Cochlear implants are currently the standard treatment for profound sensorineural hearing loss. In the last decade, advances in auditory science and technology have not only greatly expanded the utility of electric stimulation to other parts of the auditory nervous system in addition to the cochlea, but have also demonstrated drastic changes in the brain in responses to electric stimulation, including changes in language development and music perception. Auditory Prostheses: New Horizons examines a range of current issues that concern complex processing of sounds by the prosthetic device users. Advances in Auditory Prostheses - Fan-Gang Zeng. Bilateral Cochlear Implants - Richard van Hoesel Combining Acoustic and Electric Hearing - Christopher Turner and Bruce Gantz Implantable Hearing Devices for Conductive and Sensorineural Hearing Impairment - Ad Snik Vestibular Implant - Justin S. Golub, James O. Phillips, and Jay T. Rubinstein Optical Stimulation of the Auditory Nerve - Claus-Peter Richter and Angella Izzo Matic A Penetrating Auditory-Nerve Array for Auditory Prosthesis - John C. Middlebrooks and Russell L. Snyder Cochlear Nucleus Auditory Prostheses - Douglas. B. McCreery, and Steven. R. Otto Midbrain Auditory Prostheses - Hubert H. Lim, Minoo Lenarz, and Thomas Lenarz Central Auditory System Development and Plasticity after Cochlear Implantation - Anu Sharma and Michael Dorman Auditory Training for Cochlear Implant Patients - Qian-Jie Fu and John J. Galvin III Spoken and Written Communication Development Following Pediatric Cochlear Implantation - Sophie E. Ambrose, Dianne Hammes-Ganguly, and Laurie S. Eisenberg Music Perception - Hugh McDermott Tonal Languages and Cochlear Implants - Li Xu and Ning Zhou  Multisensory processing in cochlear implant listeners - Pascal Barone and Olivier Deguine About the Editors Fan-Gang Zeng is Professor and Research Director in the Department of Otolaryngology - Head & Neck Surgery, University of California, Irvine. Arthur N. Popper is Professor in the Department of Biology and Co-Director of the Center for Comparative and Evolutionary Biology of Hearing at the University of Maryland, College Park. Richard R. Fay is Distinguished Research Professor of Psychology at Loyola University Chicago. About the Series: The Springer Handbook of Auditory Research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field.